Thickening of the carotid wall. A marker for atherosclerosis in the elderly? Cardiovascular Health Study Collaborative Research Group. - O'Leary, D H; Polak, J F; Kronmal, R A; Savage, P J; Borhani, N O; Kittner, S J; Tracy, R; Gardin, J M; Price, T R; Furberg, C D (Stroke, 1996)
BACKGROUND AND PURPOSE: We investigated the relationships between prevalent coronary heart disease (CHD), clinically manifest atherosclerotic disease (ASD), and major established risk factors for atherosclerosis and intima-media thickness (IMT) in the common carotid arteries (CCA) and internal carotid arteries (ICA) separately and in combination in older adults. We wished to determine whether a noninvasive measurement can serve as an indicator of clinically manifest atherosclerotic disease and to determine which of the two variables, CCA IMT or ICA IMT, is a better correlate. METHODS: IMT of the CCA and ICA was measured with duplex ultrasound in 5117 of 5201 individuals enrolled in the Cardiovascular Health Study, a study of the risk factors and the natural history of cardiovascular disease in adults aged 65 years or more. Histories of CHD, peripheral arterial disease, and cerebrovascular disease were obtained during baseline examination. Risk factors included cholesterol levels, cigarette smoking, elevated blood pressure, diabetes, age, and sex. Relationships between risk factors and IMT were studied by multiple regression analysis and canonical variate analysis. Prediction of prevalent CHD and ASD by IMT measurements in CCAs and ICAs were made by logistic regression, adjusting for age and sex. RESULTS: IMT measurements of the CCAs and ICAs were greater in persons with CHD and ASD than those without, even after controlling for sex (P < .001). IMT measurements in the ICA were greater than those in the CCA. Risk factors for ASD accounted for 17% and 18% of the variability in IMT in the CCA and ICA, respectively. These same risk factors accounted for 25% of the variability of a composite measurement consisting of the sum of the ICA IMT and CCA IMT. The ability to predict CHD and ASD was greater for ICA IMT (odds ratio [confidence interval]: 1.36 [1.31 to 1.41] and 1.35 [1.25 to 1.44], respectively) than for CCA IMT (1.09 [1.05 to 1.13] and 1.17 [1.09 to 1.25]). CONCLUSIONS: Whereas CCA IMT is associated with major risk factors for atherosclerosis and existing CHD and ASD in older adults, this association is not as strong as that for ICA IMT. The combination of these measures relates more strongly to existing CHD and ASD and cerebrovascular disease risk factors than either taken alone.
Keywords: Adult; Aged; Arteriosclerosis; Blood Pressure; Carotid Artery, Common; Carotid Artery, Internal; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; Diabetes Mellitus; Diabetic Angiopathies; Electrocardiography; Female; Humans; Male; Medical History Taking; Physical Examination; Prospective Studies; Regression Analysis; Risk Factors; Sex Characteristics; Smoking; Tunica Intima; Tunica Media; Ultrasonography

Incidence of and risk factors for atrial fibrillation in older adults. - Psaty, B M; Manolio, T A; Kuller, L H; Kronmal, R A; Cushman, M; Fried, L P; White, R; Furberg, C D; Rautaharju, P M (Circulation, 1997)
BACKGROUND: This study aimed to describe the incidence of atrial fibrillation (AF) among older adults during 3 years of follow-up. METHODS AND RESULTS: In this cohort study, 5201 adults > or = 65 years old were examined annually on four occasions between June 1989 and May 1993. At baseline, participants answered questionnaires and underwent a detailed examination that included carotid ultrasound, pulmonary function tests, ECG, and echocardiography. Subjects with a pacemaker or AF at baseline (n=357) were excluded. New cases of AF were identified from three sources: (1) annual self-reports, (2) annual ECGs, and (3) hospital discharge diagnoses. Cox proportional-hazards models were used to assess baseline risk factors as predictors of incident AF. Among 4844 participants, 304 developed a first episode of AF during an average follow-up of 3.28 years, for an incidence of 19.2 per 1000 person-years. The onset was strongly associated with age, male sex, and the presence of clinical cardiovascular disease. For men 65 to 74 and 75 to 84 years old, the incidences were 17.6 and 42.7, respectively, and for women, 10.1 and 21.6 events per 1000 person-years. In stepwise models, the use of diuretics, a history of valvular heart disease, coronary disease, advancing age, higher levels of systolic blood pressure, height, glucose, and left atrial size were all associated with an increased risk of AF. The use of beta-blockers and high levels of alcohol use, cholesterol, and forced expiratory volume in 1 second were associated with a reduced risk of AF. CONCLUSIONS: The incidence of AF in older adults may be higher than estimated by previous population studies. Left atrial size appears to be an important risk factor, and the control of blood pressure and glucose may be important in preventing the development of AF.
Keywords: Adult; Aged; Atrial Fibrillation; Blood Glucose; Blood Pressure; Cerebrovascular Disorders; Cohort Studies; Coronary Disease; Electrocardiography; Female; Follow-Up Studies; Hospital Records; Humans; Incidence; Male; Prospective Studies; Risk Factors; United States

Association between blood pressure level and the risk of myocardial infarction, stroke, and total mortality: the cardiovascular health study. - Psaty, B M; Furberg, C D; Kuller, L H; Cushman, M; Savage, P J; Levine, D; O'Leary, D H; Bryan, R N; Anderson, M; Lumley, T (Arch Intern Med, 2001)
BACKGROUND: Recent reports have drawn attention to the importance of pulse pressure as a predictor of cardiovascular events. Pulse pressure is used neither by clinicians nor by guidelines to define treatable levels of blood pressure. METHODS: In the Cardiovascular Health Study, 5888 adults 65 years and older were recruited from 4 US centers. At baseline in 1989-1990, participants underwent an extensive examination, and all subsequent cardiovascular events were ascertained and classified. RESULTS: At baseline, 1961 men and 2941 women were at risk for an incident myocardial infarction or stroke. During follow-up that averaged 6.7 years, 572 subjects had a coronary event, 385 had a stroke, and 896 died. After adjustment for potential confounders, systolic blood pressure (SBP), diastolic blood pressure (DBP), and pulse pressure were directly associated with the risk of incident myocardial infarction and stroke. Only SBP was associated with total mortality. Importantly, SBP was a better predictor of cardiovascular events than DBP or pulse pressure. In the adjusted model for myocardial infarction, a 1-SD change in SBP, DBP, and pulse pressure was associated with hazard ratios (95% confidence intervals) of 1.24 (1.15-1.35), 1.13 (1.04-1.22), and 1.21 (1.12-1.31), respectively; and adding pulse pressure or DBP to the model did not improve the fit. For stroke, the hazard ratios (95% confidence intervals) were 1.34 (1.21-1.47) with SBP, 1.29 (1.17-1.42) with DBP, and 1.21 (1.10-1.34) with pulse pressure. The association between blood pressure level and cardiovascular disease risk was generally linear; specifically, there was no evidence of a J-shaped relationship. In those with treated hypertension, the hazard ratios for the association of SBP with the risks for myocardial infarction and stroke were less pronounced than in those without treated hypertension. CONCLUSION: In this population-based study of older adults, although all measures of blood pressure were strongly and directly related to the risk of coronary and cerebrovascular events, SBP was the best single predictor of cardiovascular events.
Keywords: Aged; Blood Pressure; Female; Humans; Male; Myocardial Infarction; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke; Survival Rate; United States